Upaya Perlindungan Anak melalui Pelatihan Keluarga Miskin dengan Anak yang Tereksploitasi Secara Ekonomi maupun Anak yang Beresiko untuk Tereksploitasi Secara Ekonomi - Adi, Isbandi Rukminto; Rahayu, Ety; Viciawati, Sari (UI Scholars Hub, 2010)
This article describes the effort in protecting children in need of special protection, especially to the family who have children in risk of being economically exploitated or children who have been economically exploitated by their parents. The problems of these children occur because they cannot access the basic services for them. This happened not only because the limited services from the government, but this could also happened because of the family life-style or the process of child rearing undertaken by their parents. Therefore this article describes the efforts in improving the resiliciency of poor family with children in the risk of being economically exploitated or children who have been economically exploitated by their parents or by their environments.